2001
DOI: 10.1523/jneurosci.21-07-02343.2001
|View full text |Cite
|
Sign up to set email alerts
|

GABA Expression Dominates Neuronal Lineage Progression in the Embryonic Rat Neocortex and Facilitates Neurite Outgrowth via GABAAAutoreceptor/ClChannels

Abstract: GABA emerges as a trophic signal during rat neocortical development in which it modulates proliferation of neuronal progenitors in the ventricular/subventricular zone (VZ/SVZ) and mediates radial migration of neurons from the VZ/SVZ to the cortical plate/subplate (CP/SP) region. In this study we investigated the role of GABA in the earliest phases of neuronal differentiation in the CP/SP. GABAergic-signaling components emerging during neuronal lineage progression were comprehensively characterized using flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
118
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(118 citation statements)
references
References 58 publications
0
118
0
Order By: Relevance
“…Along with changes in the level of expression, we showed that GABA A R activation in precursors and neuroblasts leads to different physiological outcomes, that is, in neuroblasts it induces depolarization and a rise in Ca 2þ levels, whereas in precursors it is hyperpolarizing and does not increase [Ca 2þ ] i , suggesting that the Cl À gradient is different in these two cell types [35]. This result further highlights the similarity between neonatal SEZ precursors and the embryonic neocortex, where the depolarizing effect of GABA along with increase in [Ca 2þ ] i are primarily confined to cells undergoing neuronal differentiation [36]. Consistent with the opposite effects on membrane potential in the two cell types, osmotic swelling was not observed in neuroblasts but only in precursors, and in particular, in cells expressing prominin.…”
Section: Discussionmentioning
confidence: 76%
“…Along with changes in the level of expression, we showed that GABA A R activation in precursors and neuroblasts leads to different physiological outcomes, that is, in neuroblasts it induces depolarization and a rise in Ca 2þ levels, whereas in precursors it is hyperpolarizing and does not increase [Ca 2þ ] i , suggesting that the Cl À gradient is different in these two cell types [35]. This result further highlights the similarity between neonatal SEZ precursors and the embryonic neocortex, where the depolarizing effect of GABA along with increase in [Ca 2þ ] i are primarily confined to cells undergoing neuronal differentiation [36]. Consistent with the opposite effects on membrane potential in the two cell types, osmotic swelling was not observed in neuroblasts but only in precursors, and in particular, in cells expressing prominin.…”
Section: Discussionmentioning
confidence: 76%
“…Another possibility, however, is that GABA A receptors serve a trophic role in the growth cone and young synapse, sensing ambient GABA, which could enhance axonal outgrowth. Such a model has been proposed for somatodendritic GABA A receptors in migrating neurons (36,37). Here, GABA A receptor activation leads to weak depolarization and calcium influx through voltage-dependent Ca channels.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this theory, GABA A receptor antagonists (e.g. bicuculline) or agents that block GABA synthesis inhibit neuritic arborization of cortical neurons (Ben-Ari et al, 1994;Maric et al, 2001). Thus, a deficiency in GABA A receptors may perturb the maturation of the inhibitory neural network, in spite of elevated GABA levels that encourage axonal and dendritic development.…”
Section: Gabaergic Protein Expression and Neuronal Development In Thementioning
confidence: 98%
“…Chronic GABA A receptor activation in early development is necessary for the switch from GABA excitation to inhibition in the brain (Ganguly et al, 2001) and in the retina (Leitch et al, 2005). Furthermore, GABA itself promotes neurite length and branching in inhibitory and excitatory cortical neurons from neonatal rats and embryonic chicks (Baloyannis et al, 1983;Spoerri, 1988;Maric et al, 2001). In Fmr1 knockout mice, the dysregulation of GABA A receptor and GABAergic enzyme expression may affect GABA-mediated activity during the critical period.…”
Section: Gabaergic Protein Expression and Neuronal Development In Thementioning
confidence: 99%